2017
DOI: 10.1063/1.4986497
|View full text |Cite
|
Sign up to set email alerts
|

Defect analysis in GaN films of HEMT structure by cross-sectional cathodoluminescence

Abstract: Defect analysis of GaN films in high electron mobility transistor (HEMT) structures by cross-sectional cathodoluminescence (X-CL) is demonstrated as a useful technique for improving the current collapse of GaN-HEMT devices, and the relationship between crystal quality and device characteristics is also investigated. The crystal quality of intrinsic-GaN (i-GaN) and carbon-doped GaN produced clearly different peak intensities of blue luminescence (BL), yellow luminescence (YL), and band-edge emission (BE), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…2(a), the spectrum of the LPJ MQWs identifies two main peaks: one is located at ∼343 nm consistent with the PL (Fig. 1) attributed to the MQW emission; and the broad peak is related to deep levels such as donor-acceptor pair or transition from conduction band to deep acceptors [11]. The shorter wavelength of the CL MQW peak compared to that of the PL peak may be attributed to the band filling effect due to much higher excitation electron energy amid CL experiments.…”
Section: Resultssupporting
confidence: 53%
“…2(a), the spectrum of the LPJ MQWs identifies two main peaks: one is located at ∼343 nm consistent with the PL (Fig. 1) attributed to the MQW emission; and the broad peak is related to deep levels such as donor-acceptor pair or transition from conduction band to deep acceptors [11]. The shorter wavelength of the CL MQW peak compared to that of the PL peak may be attributed to the band filling effect due to much higher excitation electron energy amid CL experiments.…”
Section: Resultssupporting
confidence: 53%
“…[22] In this review, the until then identified PL bands in GaN are described and a detailed summary of their behavior, e.g., dependence on temperature, excitation power density, and doping, is given. Emanating from the importance of C doping for optoelectronic devices and the fact that luminescence methods are more and more often applied for device analysis, [11,[23][24][25][26][27] in this article we focus on the recent progress with respect to understanding the role of C in bulk GaN. Accordingly, we will emphasize the defect-related radiative transitions in the visible spectral region of carbon-doped bulk GaN.…”
mentioning
confidence: 99%